2023
DOI: 10.3389/fimmu.2023.1159831
|View full text |Cite
|
Sign up to set email alerts
|

Impaired alveolar macrophage 11β-hydroxysteroid dehydrogenase type 1 reductase activity contributes to increased pulmonary inflammation and mortality in sepsis-related ARDS

Abstract: BackgroundAcute Respiratory Distress Syndrome (ARDS) is a devastating pulmonary inflammatory disorder, commonly precipitated by sepsis. Glucocorticoids are immunomodulatory steroids that can suppress inflammation. Their anti-inflammatory properties within tissues are influenced by their pre-receptor metabolism and amplification from inactive precursors by 11β-hydroxysteroid dehydrogenase type-1 (HSD-1). We hypothesised that in sepsis-related ARDS, alveolar macrophage (AM) HSD-1 activity and glucocorticoid acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…It had been previously shown that Toll-like receptor 4 (TLR4) activation by LPS contaminants in HDM extracts and the subsequent release of cytokines and chemokines is indispensable for allergen sensitization, with low doses of LPS promoting a Th2-type eosinophilic immune reaction, whereas high doses of LPS rather initiate a Th17-type neutrophilic response ( 36 40 ). In line with this, direct intra-tracheal administration of LPS led to increased neutrophil infiltration into the alveolar space of KO mice ( 41 ). Interestingly, the lack of local 11β-HSD1-mediated GC reactivation does not seem to affect the type 2 phenotype in the acute HDM model, but causes a mixed type 2/type 17 phenotype with enhanced neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 65%
“…It had been previously shown that Toll-like receptor 4 (TLR4) activation by LPS contaminants in HDM extracts and the subsequent release of cytokines and chemokines is indispensable for allergen sensitization, with low doses of LPS promoting a Th2-type eosinophilic immune reaction, whereas high doses of LPS rather initiate a Th17-type neutrophilic response ( 36 40 ). In line with this, direct intra-tracheal administration of LPS led to increased neutrophil infiltration into the alveolar space of KO mice ( 41 ). Interestingly, the lack of local 11β-HSD1-mediated GC reactivation does not seem to affect the type 2 phenotype in the acute HDM model, but causes a mixed type 2/type 17 phenotype with enhanced neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 65%
“…GC are well-known for their anti-inflammatory effects, supporting our observed induction of pro-inflammatory genes and pathways by AZD4017. Importantly, this has not translated to adverse outcomes during mild / acute inflammation [7,11,24], but could be disadvantageous during severe / chronic inflammation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…AMs were resuspended in RPMI1640 containing 10% FBS, 100U/mL penicillin, 100µg/mL streptomycin and 2mM L-glutamine (Sigma-Aldrich), and plated. This method generates primary human alveolar macrophages with purity >98% as measured by a validated combination of cytospin and flow cytometry using antibodies against CD68 ( 81 ).…”
Section: Methodsmentioning
confidence: 99%